El juego y la motricidad gruesa en los niños de 4 a 5 años de la escuela de educación básica iv Centenario ubicada en la ciudad de Loja, en el período 2019 – 2020. - Espinoza Asanza, Mery Priscila (2021)
Due to the current importance of obtaining optimal development in students, this research is entitled: GAME AND GROSS MOTOR IN CHILDREN FROM 4 TO 5 YEARS OLD FROM THE IV CENTENARY SCHOOL OF BASIC EDUCATION LOCATED IN THE CITY OF LOJA, IN THE PERIOD 2019 - 2020., had as a general objective to analyze the importance of games in gross motor skills in children from 4 to 5 years old. The study worked with a sample of 21 people, that is, 1 teacher and 20 children, using non-probability sampling. Using a non-experimental design, a mixed approach, a descriptive scope, a descriptive statistic and the methods were used: analytical-synthetic and inductivedeductive. To obtain information on the variables, an interview was applied to the teacher and the Abbreviated Development Scale (EAD-1) of Nelson Ortiz to the children, in which they failed in most of the items in the area of gross motor skills, aspect that allows to focus on the diagnosed problem, showing that 90% of the population investigated are at a medium and alert level, with difficulties in activities such as standing on one foot, walking in a straight line, jumping and bouncing, throwing and catch the ball, which is why an alternative proposal was designed with different games to work, stimulate and strengthen the development of gross motor skills, allowing the student to acquire greater control of their own body and mastery of motor skills